The Simulation Model of Dengue Transmission by Gender of Human in Thailand - Puntipa Pongsumpun; Puntani Pongsumpun (My University, 2023)
Dengue disease can be transmitted to human by the biting of infected Aedes aegypti mosquitoes. This disease has 4 serotypes such as DEN-1, DEN-2, DEN-3 and DEN-4. The symptoms of this disease are high fever, headache, body aches, nausea and rash. This paper describes the spread of this disease by formulating the dynamical model between human and mosquito populations. The human are separating into man and woman populations. The standard dynamical modelling method is used to analyze our dynamical model. The numerical solutions are presented. The basic reproduction value of the disease is found. The way for reducing the transmission of this disease is introduced.
Keywords: Basic reproduction number; Human disease; Disease Transmission; Mathematical and Theoretical Epidemiology and Ecology Models